2010
DOI: 10.1111/j.1743-6109.2010.01765.x
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Testosterone Undecanoate (Nebido®) in Testosterone Deficiency Syndrome in Korean: A Multicenter Prospective Study

Abstract: Introduction Long-acting injectable testosterone undecanoate (TU, Nebido®), a new parenteral testosterone preparation, has recently been introduced to avoid frequent injections of the conventional injectable esters. Aims To assess the efficacy and safety of long-acting injectable testosterone undecanoate (TU, Nebido®) in Korean patients with testosterone deficiency syndrome (TDS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 24 publications
3
38
0
11
Order By: Relevance
“…The results indicated that testosterone undecanoate was effective, safe and tolerable. 55 For premature ejaculation, psychological and behavioural therapy, local anaesthetic creams, SS creams, tramadol and selective serotonin reuptake inhibitors can be used. Dapoxetine, a new short-acting selective serotonin reuptake inhibitor that has fewer side effects than longer-acting selective serotonin reuptake inhibitors, has been recently introduced.…”
Section: Treatmentmentioning
confidence: 99%
“…The results indicated that testosterone undecanoate was effective, safe and tolerable. 55 For premature ejaculation, psychological and behavioural therapy, local anaesthetic creams, SS creams, tramadol and selective serotonin reuptake inhibitors can be used. Dapoxetine, a new short-acting selective serotonin reuptake inhibitor that has fewer side effects than longer-acting selective serotonin reuptake inhibitors, has been recently introduced.…”
Section: Treatmentmentioning
confidence: 99%
“…Существующие препараты отличаются по пути вве-дения и фармакокинетическим особенностям, решение о выборе конкретного препарата должно приниматься врачом и пациентом совместно [50,51].…”
Section: выбор методов леченияunclassified
“…В большинстве ретроспективных исследований был зафиксирован благоприятный эффект в отношении ли-бидо, эрекции и эякуляции (уровень 2a, степень A) [76,77]. Международное многоцентровое проспективное ис-следование с участием 1493 мужчин показало, что ТЗТ достоверно улучшает либидо, эректильную функцию и ответ на терапию ингибиторами фосфодиэстеразы 5-го типа, часто используемыми при лечении ЭД на фоне СД [18,78,79].…”
Section: благоприятные эффекты леченияunclassified
“…In a recent prospective study from nine andrological centres involving 133 Korean patients, injectable TU significantly decreased cholesterol, improved total IIEF scores and all five IIEF domain scores, and improved total AMS scores and all three AMS subscales. 39 While TU caused significantly elevated levels of haemoglobin, haematocrit and prostate-specific antigen (PSA) at 24 weeks, serum TT levels were maintained within normal ranges, and no serious adverse reactions were observed.…”
Section: Intramuscular Injectionmentioning
confidence: 99%
“…In four Korean prospective trials containing data on serial changes in serum PSA levels, two studies found no alterations 34,38 in serum PSA levels, and two studies found significant increases in serum PSA levels after intramuscular TU injection. 39,52 Lee et al 52 followed 47 Korean TRT patients for a mean period of 7.9 months. The patients were classified into two groups based on their initial PSA levels of either above (Group 1) or below 2.5 ng ml 21 (Group 2) PSA.…”
Section: Intramuscular Injectionmentioning
confidence: 99%